B-C activation in highly alkylated carborane monoanions partnered with cationic transition metal fragments: observations and comments - Ingleson, M; Kociok-Kohn, G; Weller, A (2005)
Cage decomposition products of the highly methylated, weakly coordinating, carborane anion [1-H-closo-CB11Me11]- are described. These arise both from well-defined metal complexes of [1-H-closo-CB11Me11]- that already have BCH3⋯[M] interactions and from attempts to partner this anion with other metal centres. In all cases the decomposition results in B-CH 3 bond cleavage and solvent activation to form products with B-aryl or B-Cl vertices. © 2004 Published by Elsevier B.V.